Morphogenesis, pigment content, phytohormones and productivity of eggplants under the action of gibberellin and tebuconazole - V. V. Rogach; L. V. Voytenko; M. M. Shcherbatiuk; I. V. Kosakivska; T. I. Rogach (Regulatory Mechanisms in Biosystems, 2020)
Regulation of growth and development of cultivated plants in order to optimize the production process is one of the main objectives of modern plant physiology. Both activators and growth inhibitors are used for this purpose. The effect of foliar treatment with 0.005% solution of gibberellic acid and 0.025% solution of antigibberellic preparation of tebuconazole on the morphogenesis, leaf structure, photosynthetic pigment content, balance of phytohormones and eggplant productivity cv. Diamond variety was investigated. The treatment with the preparations was carried out in the budding phase. The vegetation experiment was laid under soil and sand culture in vessels of a ten-liter capacity. The morphometric parameters were determined every 10 days, the mesostructure was studied in the leaves of the middle tier in the phase of fruit formation, chlorophyll content was measured in the raw material by spectrophotometric method. Analytical determination of phytohormones (indole-3-acetic acid, gibberellic, abscisic acids and cytokinins – zeatin, zeatin-O-glucoside, zeatinriboside, isopentenyladenine and isopentenyladenosine) was performed by high performance liquid chromatography. Under the action of gibberellic acid, plant height increased significantly, and it decreased after its treatment with tebuconazole. The stimulator and inhibitor increased the number of leaves per plant, the weight of the leaf dry matter, the area of the individual leaf blade and the area of leaves per plant. Both preparations increased the weight of the raw material of the stems and roots, as well as the mass of dry matter of the whole plant. Under the action of tebuconazole, the content of chlorophylls in the leaves increased, while under the action of gibberellic acid it decreased. After treatment with gibberellic acid and tebuconazole, the thickness of the leaf blade increased due to chlorenchyma thickening. In the variant with gibberellic acid, the thickness of upper and lower epidermis increased, and in the variant with tebuconazole, these parameters decreased. Both growth regulators increased the volume of cells of the columnar parenchyma. The contet of endogenous gibberellic, indole-3-acetic and abscisic acids of the stems and especially in the leaves increased with the treatment of exogenous gibberellic acid, whereas after the application of tebuconazole the gibberellic and indole-3-acetic acid content of the stems decreased significantly and practically decreased to traces. Instead, the amount of abscisic acid increased. After treatment with exogenous gibberellic acid, the pool of cytokinins in the leaves significantly decreased. The inactive isoforms of the hormone zeatin-O-glucoside and isopentenyladenosine dominated in the stems. The effect of tebuconazole decreased the pool of cytokinins in the stems and increased in the leaves. In general, due to the multidirectional action, growth regulators positively influenced the elements of eggplant productivity. More effective was the retardant – tebuconazole. Therefore, the anatomic-morphological and structural-functional rearrangements in eggplants under the effects of exogenous gibberellic acid and tebuconazole are due to changes in the balance and distribution of endogenous hormones. Increased photosynthetic activity, stimulation of growth processes of some organs of the plant and inhibition of others enlarged the biological productivity of the culture.